Unilateral biportal endoscopic lumbar interbody fusion vs. posterior lumbar interbody fusion for the treatment of bilateral lumbar spinal stenosis - Dong, Renjie; Wu, Shan; Zhong, Dian; Zhao, Guosheng; Liu, Yang; Wang, Yang (Frontiers in Surgery, 2025)
ObjectiveThis study aimed to evaluate the clinical efficacy and safety of unilateral biportal endoscopic lumbar interbody fusion (UBE-LIF) and posterior lumbar interbody fusion (PLIF) for treating patients with lumbar spinal stenosis with bilateral radiating symptoms. All the patients included in the study had single-segment lumbar spinal stenosis.MethodsFrom January 2021 to June 2023, 21 patients with lumbar spinal stenosis treated with UBE-LIF and 29 patients with lumbar spinal stenosis treated with PLIF were retrospectively analyzed. Clinical differences in demographic characteristics, surgical details, preoperative and postoperative visual analog scale (VAS) scores, Oswestry Disability Index (ODI) score, MacNab criteria, and complications were analyzed.ResultsA total of 50 patients were included in this study. There were no differences in demographic characteristics and MacNab criteria between the two groups (P > 0.05). The operation time in the UBE-LIF group was significantly longer than that in the PLIF group (P < 0.05). Hemoglobin loss in the UBE-LIF group was significantly lower than the PLIF group, as were postoperative drainage volume and hospitalization days (P < 0.05). The postoperative VAS and ODI scores were significantly lower than those before the respective operations in both groups. The VAS and ODI scores in the UBE-LIF group were significantly lower than those in the PLIF group 1 week after the respective operations (P < 0.05).ConclusionsUBE-LIF was able to achieve the same bilateral decompression as PLIF and resulted in better symptomatic improvement in the early postoperative period, which may be related to it resulting in less damage to the back muscle tissue. This study suggests that UBE-LIF may be a minimally invasive alternative to PLIF.